Pazopanib and Liposomal Doxorubicin in the Treatment of Patients with Relapsed/Refractory Epithelial Ovarian Cancer: A Phase Ib Study of the Sarah Cannon Research Institute. (16th March 2015) - Hainsworth, John D.; Firdaus, Irfan D.; Earwood, Chris B.; Chua, Cynthia C.
Abstract : Purpose : To investigate the combination of liposomal doxorubicin/pazopanib in advanced relapsed/refractory ovarian cancer. Patients and Methods : Twenty-two patients received liposomal doxorubicin/pazopanib. Initial doses (liposomal doxorubicin, 40 mg/m 2 monthly; pazopanib, 400 mg daily) were too toxic; three subsequent groups received lower doses/altered schedules. Results : The maximum tolerated doses (MTD) were liposomal doxorubicin, 30 mg/m 2, and pazopanib, 400 mg daily. Severe toxicity included neutropenia (18%), rash/desquamation (14%), hypertension (9%), and hand–foot syndrome (9%). Five of the eight patients treated with MTD had grade 3 toxicity during the first two cycles. Dose reductions were frequently required. Conclusions : Further development of the liposomal doxorubicin/pazopanib combination is not recommended.